Vocabulary Learning Strategies in Learning New Words for EFL Learners Based on Gender Differences - Novia Putri Riyantika; Hanafi Hanafi; Kristi Nur Aini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study investigates vocabulary learning strategies (VLS) among male and female EFL learners at Muhammadiyah University Jember. Using questionnaires and interviews, the research explores gender differences in discovering and consolidating new vocabulary. The findings reveal that both genders primarily use dictionaries for discovery, with males preferring visual aids and females relying on social interactions. For consolidation, males favor spaced repetition and word lists, while females use mnemonics and narrative techniques. These insights highlight the need for differentiated instruction to accommodate diverse learning preferences.